Sexual health promotion programme: Participants' perspectives on capacity building. (February 2016) - Keogh, Brian; Daly, Louise; Sharek, Danika; De Vries, Jan; McCann, Edward; Higgins, Agnes
Objectives: The aim of this study was to evaluate a Health Service Executive (HSE) Foundation Programme in Sexual Health Promotion (FPSHP) with a specific emphasis on capacity building. Design: A mixed-method design using both quantitative and qualitative methods was used to collect the data. Setting: The FPSHP was delivered to staff working in health, education and community settings and was designed and facilitated by sexual health promotion staff who are part of the Irish HSE. Methods: A survey, designed by the researchers, as well as individual telephone interviews with past participants was used to evaluate the programme. Out of a possible 200 participants, 97 completed the questionnaire (response rate 49%), and a total of 22 telephone interviews were completed. Results: There was generally a high level of satisfaction with the FPSHP. Participants reported high levels of individual and intra-organisational capacity-building activities, but apart from networking, inter-organisational capacity-building activities were reported less frequently and tended to be ad hoc in nature. Satisfaction with the programme was high and so was the perception of its sustained impact. Motivation, satisfaction with the programme and attending of further training were strong predictors of reported sustained impact. Conclusion: Capacity building in sexual health promotion was affected positively by participation in the programme. Nonetheless, a greater emphasis on capacity building at an inter-organisational level needs to be considered. It is recommended that participants need to be motivated, guided and supported in the use of strategies to achieve this.